Jak i dlaczego badać współczesną powieść kryminalną? = How and why study modern crime novels? Reflections on social crime fiction - Gazdecka, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses issues related to methodology used by Polish researchers focusing on crime novels. It describes a new evolutionary direction - social crime stories. The new direction enforces the adjustment of modern research methodology in order to include both the cultural context of the plot and the value system of the characters. The latter is one of the clearest windows that allows the inspection of prezent-day reality.
Keywords: powieść kryminalna; badania literackie; metodologia